The origin and evolution of phototropins - Li, Fay-Wei; Rothfels, Carl J.; Melkonian, Michael; Villarreal, Juan C.; Stevenson, Dennis W.; Graham, Sean W.; Wong, Gane K.-S.; Mathews, Sarah; Pryer, Kathleen M. (Frontiers in Plant Science, 2015)
Plant phototropism, the ability to bend toward or away from light, is predominantly controlled by blue-light photoreceptors, the phototropins. Although phototropins have been well-characterized in Arabidopsis thaliana, their evolutionary history is largely unknown. In this study, we complete an in-depth survey of phototropin homologs across land plants and algae using newly available transcriptomic and genomic data. We show that phototropins originated in an ancestor of Viridiplantae (land plants + green algae). Phototropins repeatedly underwent independent duplications in most major land-plant lineages (mosses, lycophytes, ferns, and seed plants), but remained single-copy genes in liverworts and hornworts—an evolutionary pattern shared with another family of photoreceptors, the phytochromes. Following each major duplication event, the phototropins differentiated in parallel, resulting in two specialized, yet partially overlapping, functional forms that primarily mediate either low- or high-light responses. Our detailed phylogeny enables us to not only uncover new phototropin lineages, but also link our understanding of phototropin function in Arabidopsis with what is known in Adiantum and Physcomitrella (the major model organisms outside of flowering plants). We propose that the convergent functional divergences of phototropin paralogs likely contributed to the success of plants through time in adapting to habitats with diverse and heterogeneous light conditions.